Utopistyczny wymiar rozwoju zrównoważonego - Płachciak, Adam (Annales. Etyka w Życiu Gospodarczym, 2011)
Utopian consciousness is defined as an expression of opposition against actual status quo with simultaneous tendency towards creatingalternative projects guarantying possibilities which are not found in actual reality. Utopias usually are recognized as negative concepts.They may often glare with simple and artificial examples or faith their believers in realization of imagined world. Utopists are often calleddreamers and people who try to implement unreal ideas into life.Although it can not be forgotten that there is a meaningful difference between abstract utopia and concrete one. In concrete utopia allwishful thinking is changed by seeking real historical alternatives in the boundaries of existed social, political and economical possibilities.If the history of social thought improves that utopias include inspiring force, expose weaknesses of actual order, criticize status quo it shouldbe asked if the idea of sustainable development does not include some elements of utopian thought.